Metode Pembelajaran Aktif dan Kreatif pada Madrasah Diniyah Takmiliyah di Kota Bogor - Ariep Hidayat; Maemunah Sa'diyah; Santi Lisnawati (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
The issue in this research is how is the learning method applied in Madrasah Diniyah Takmiliyah Al Ghazaly Bogor ? To that end, this study aims to describe the learning methods applied in Madrasah Diniyah Takmiliyah Al Ghazaly Bogor. This study uses descriptive qualitative method with primary data collection through in-depth interviews and observation while secondary is data obtained through documentation.The study showed that The application of learning methods in Madrasah Diniyah Takmiliyah Al Ghazaly Bogor has not been effective because it still uses conventional methods like lecture methods, discussion methods, demonstration methods, and Resitation methods. There needs to be a variety of learning methods so that the learning process is active, creative and enjoyable.